Cost of quality used in the management strategy of technology companies (Research, Society and Development, 2020)
Through a qualitative research in two case studies, we sought to comparatively evaluate the quality costing methods in relation to the theoretical framework on the ideal costing method with the quality costs in an organization. Being this management of paramount importance and a key element for the development and business growth, therefore, will be a differential over competing companies. Thus identifying the best strategies to be used in the management of quality costs, providing the identification of opportunities to improve the operational performance of the organization. Therefore, we seek to understand the costing tool through two case studies, using process mapping and quality costing (CDQ) from two organizations. As a preliminary analysis of the data in “Company 1”, there is the initial investment in prevention (0.29% of monthly revenues) and evaluation (0.24% of monthly revenues) in the search for reduction of internal and external failure costs, which These initially represent 0.64% of the company's monthly revenues. In “Company 2”, the initial costs of prevention (0.03% of monthly revenues) and evaluation (3.91% of monthly revenues) tried to obtain better results in failure costs, but without success the costs worsened from 0.65% to 1.06% in the sum of internal and external failures. Thus, the possibility of studying the costing methods employed and the theoretical comparison with the ideal costing method of quality costs is well known. Allowing a critical analysis of situations.